Comparative Study of Intraocular Pressure Changes with Laryngeal Mask Airway and Endotracheal Tube - Malti J. Pandya; Geeta Agarwal (Medsci Publications, 2012)
Aims: To evaluate the intraocular pressure changes subsequent to insertion and removal of laryngeal mask airway and endotracheal tube. Methods: The study was conducted in 60 adult patients. A standard general anaesthesia was administered to all patients, after induction of anaesthesia baseline measurements of intraocular pressure was taken, following which patients were divided into two groups. In group-I, airway secured with endotracheal tube and in group -II, with the laryngeal mask airway. Intraocular pressure measurements were done after induction and repeated immediately, three and six minutes after intubation with endotracheal tube or laryngeal mask airway insertion. At the end of surgery, intraocular pressure was measured again, immediately after reversal and three minutes after removal of endotracheal tube or laryngeal mask airway. The intraocular pressure measured after induction of anaesthesia was compared with intraocular pressure values in two groups at different intervals. Results: A statistically significant increase in intraocular pressure was seen in group-I (ETT) as compared to group- II (LMA) (p<0.001) immediately after securing airway and also at the end of surgery immediately after reversal and three minutes after removal of endotracheal tube or laryngeal mask airway. Conclusion: Use of laryngeal mask airway might offer advantages in patients where minimal changes in intraocular pressure are desirable.